SCREENING OF MARINE VIBRIO SP ISOLATED FROM THE BAY OF BENGAL, INDIA FOR CHITINASE ENZYME PRODUCTION - VINAYAGAM RAVIKUMAR; SUNDARAM MEIGNANALAKSHMI (International Journal of Pharma and Bio Sciences, 2013)
A total of 12 water, sediment and plankton samples were collected from different sampling stations of open sea off the Bay of Bengal coast of Chennai, Tamilnadu, India and 160 isolates of marine Vibrio sp were isolated using Thiosulphate Citrate Bile Sucrose (TCBS) agar medium. The entire isolates were screened for the production of chitinase enzyme on to colloidal chitin agar plates. One of these strains with high ability to produce chitinase was selected and identified as Vibrio alginolyticus JN863235 by morphological and biochemical properties along with 16S rDNA partial gene sequence analysis. The production of chitinase by Vibrio alginolyticus JN863235 was optimized using different substrate concentrations, pH, and temperature and incubation period. The maximum chitinase production was observed with 0.6% colloidal chitin at pH 6.5 at temperature 30°C after 3 days incubation. Whereas the chitinase production on the media containing colloidal chitin and its combination with glucose, yeast extract, K2HPO4 showed that the highest activity 19.31, 19.28, 17.11 U/ml respectively was achieved on day 3.